2022
DOI: 10.1111/pbi.13823
|View full text |Cite
|
Sign up to set email alerts
|

PPVED: A machine learning tool for predicting the effect of single amino acid substitution on protein function in plants

Abstract: Single amino acid substitution (SAAS) produces the most common variant of protein function change under physiological conditions. As the number of SAAS events in plants has increased exponentially, an effective prediction tool is required to help identify and distinguish functional SAASs from the whole genome as either potentially causal traits or as variants. Here, we constructed a plant SAAS database that stores 12 865 SAASs in 6172 proteins and developed a tool called Plant Protein Variation Effect Detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…In line with this, substitutions between B73 and mexicana were predicted to be neutral (http://www. ppved.org.cn/) (Figure S3b) (Gou et al, 2022). Therefore, the different effects of ZmDRO1 B73 and ZmDRO1 mex may be resulting from the transcriptional level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, substitutions between B73 and mexicana were predicted to be neutral (http://www. ppved.org.cn/) (Figure S3b) (Gou et al, 2022). Therefore, the different effects of ZmDRO1 B73 and ZmDRO1 mex may be resulting from the transcriptional level.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple sequence alignment of orthologous genes of DRO1 from 18 species showed that all four amino acid substitutions in ZmDRO1 between B73 and mexicana were not conserved (Figure S3 a). In line with this, substitutions between B73 and mexicana were predicted to be neutral ( http://www.ppved.org.cn/ ) (Figure S3 b) (Gou et al ., 2022 ). Therefore, the different effects of ZmDRO1 B73 and ZmDRO1 mex may be resulting from the transcriptional level.…”
Section: Resultsmentioning
confidence: 99%
“…Ala161 is present in all canonical HSP70 family members (DnaK-homologues) across bacteria, archaea, and eukaryotes, but varies in non-canonical HSP70- related gene families, such as bacterial HSCA/Cs and HSP110s. Two computational tools, PredictSNP (Bendl et al 2014) and PPVED (Gou et al 2022), both predicted a deleterious effect of an A to T substitution on protein function (Fig S7). Further, severe deleterious effects resulting from an A to T substitution within an alpha-helix of an Arabidopsis kinase have been reported (Piovesana et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PROVEAN (PROtein Variant Effect ANalyzer) v1.1.5 [60], SIFT4G [61] and PPVED [62] predicted whether an amino acid substitution affected protein function.…”
Section: Gomentioning
confidence: 99%